-119C/G in MYG1 Gene and 49A/G in CTLA4 Gene Polymorphisms in Turkish Patients with Vitiligo - Yildiz, Saliha Handan; Yildirim, Ayşen; Özuğuz, Pınar; Özdemir Erdoğan, Müjgan; Doğruk Kaçar, Seval; Arikan Terzi, Evrim Suna; Kuşku, Elvin; Söylemez, Zafer; Solak, Mustafa (Journal of Advances in Internal Medicine, 2017)
Vitiligo is a disease characterized by sharply limited white macular depigmentation as a result of melanocyte loss. Disease is divided into three types according to prevalence and localization as localized, general and universal. Etiology of vitiligo is unknown, but clearly shows a complex structure. Genetic predisposition, stress, many influencing factors such as systemic diseases and physical trauma causes vitiligo. In our study, MYG1 gene rs1465073 (-119C/ G) and CTLA4 gene rs231775 (49A/G) polymorphisms were evaluated in 106 patients diagnosed with vitiligo and 97 controls. Genotyping was performed using real time PCR method. There is no statistically significant differences between patients and controls in terms of allele frequencies of MYG1gene rs1465073 and ve CTLA4 gene rs231775 polymorphisms. Beside, there is no statistically significant differences between patients and controls in terms of genotype frequencies of CTLA4 gene rs231775 polymorphism. On contrary to this there is statistically significant differences between patients and controls in terms of genotype frequencies of MYG1gene rs1465073 polymorphism. In conclusion, consistent with the literature data, there is a significant association between MYG1gene rs1465073 polymorphism and vitiligo. But there is no directly association between CTLA4 gene rs231775 polymorphism and vitiligo. Journal of Advances in Internal Medicine 2016;05(01):1-5